Potentially lactic acid bacteria as an EPS producing starter from yellow sweet potato fermentation - NETI YULIANA; Sumardi SUMARDI; EDO JATMIKO; MENTARI ROSALINE; MUHAMMAD IQBAL (Society for Indonesian Biodiversity, 2020)
Potentially lactic acid bacteria as a starter for EPS production from yellow sweet potato fermentation were determined. The fermentation profile and partial characteristics of isolated lactic acid bacteria were used as considerations. The fermentation of yellow sweet potato was performed in the back-slopping and spontaneous procedure and was paid attention to the hours of 0, 24, 48, and 72.  The results showed that the 72 hours of fermentation was found to have the highest EPS metabolites, the number of a LAB, the total lactic acid, and the lowest pH. The 72 hours of fermentation also seemed to cause a significant change in the sweet potato starch granules morphology.   The potential starter, therefore, can be taken from the yellow sweet potato fermentation either spontaneously or by a back-slopping method, at 72 hours. From the sixty selected LAB, the 34 strains showed an ability to produce EPS. Among these, eight strains exhibited the potential high production of  EPS.  They were capable of growth on 28-45C and exhibited tolerance to 3-4% NaCl. The favorable carbon sources for the growth and production of EPS were isolated dependent.